Differences in air drag among elite male alpine skiers - Supej, M.; Saetran, L.; Oggiano, L.; Ettema, G.; Holmberg, H. C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Alpine ski racing is a complex sport in which energy dissipation is one of the crucial performance predicting parameters (Supej et al., 2010). The main factors in energy dissipation are air drag and ski-snow friction. To our knowledge, air drag cannot be directiy measured during skiing. Therefore, in order to be able to understand the performance differences that can be measured in technical skiing disciplines, it is of interest to examine the size of the differences in air drag among elite ski racers.